2014
DOI: 10.4238/2014.march.26.8
|View full text |Cite
|
Sign up to set email alerts
|

Association of neural tube defects in children of mothers with MTHFR 677TT genotype and abnormal carbohydrate metabolism risk: a case-control study

Abstract: ABSTRACT. Abnormalities in maternal folate and carbohydrate 2201©FUNPEC-RP www.funpecrp.com.br Genetics and Molecular Research 13 (1): 2200-2207 (2014) Combination of risk factors in spina bifida metabolism have both been shown to induce neural tube defects (NTD) in humans and animal models. However, the relationship between these two factors in the development of NTDs remains unclear. Data from mothers of children with spina bifida seen at the Unidad de Espina Bífida del Hospital Infantil Virgen del Rocío … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
1
6
0
4
Order By: Relevance
“…This phenotype has not been found previously in this mutant mouse line, although it was associated with NTDs in human patients . Interestingly, studies in humans revealed that mothers homozygous for the MTHFR C677T polymorphism (MTHFR6TT, but not MTHFR 677CT) and at risk of abnormal carbohydrate metabolism had a higher risk of bearing offspring with spina bifida . In the knowledge that this polymorphism is associated with decreased enzyme activity and an increase in blood homocysteine levels our data are also consistent with the idea that only a severe impairment in maternal folate metabolism is capable of inducing NTDs along with maternal diabetes.…”
Section: Discussionsupporting
confidence: 91%
“…This phenotype has not been found previously in this mutant mouse line, although it was associated with NTDs in human patients . Interestingly, studies in humans revealed that mothers homozygous for the MTHFR C677T polymorphism (MTHFR6TT, but not MTHFR 677CT) and at risk of abnormal carbohydrate metabolism had a higher risk of bearing offspring with spina bifida . In the knowledge that this polymorphism is associated with decreased enzyme activity and an increase in blood homocysteine levels our data are also consistent with the idea that only a severe impairment in maternal folate metabolism is capable of inducing NTDs along with maternal diabetes.…”
Section: Discussionsupporting
confidence: 91%
“…Spina bifida, eine Verschlussstörung der Wirbelsäule [5], ist die am weitesten verbreitete Fehlbildung des Neuralrohrs [8]. Sie tritt bei durchschnittlich 10/10 000 Geburten auf [9]. Ein Risikofaktor stellt das Alter der Mutter dar.…”
Section: Hintergrundunclassified
“…Zwischen den 16 Bundesländern zeigen sich keine erheblichen Unterschiede im Auftreten der 4 zusammengefassten Fehlbildungen. Auffallend sind jedoch die vergleichsweise niedrige Prävalenz in Berlin (9,41/10 000 LB, KI 8,4-10,5) und das scheinbar gehäufte Auftreten von angeborenen Fehlbildungen in Mecklenburg-Vorpommern (17,41/10 000 LB, KI 15,[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]6). Ursache dafür ist wahrscheinlich der Fehler der kleinen Zahlen, also eine Verfälschung des Ergebnisses aufgrund einer geringen Gesamtmenge.…”
Section: Ergebnisseunclassified
See 1 more Smart Citation
“…NTDs (Neural tube defects) are a group of severe, disabling and deadly congenital disorders of the nervous system, arising from incomplete neural tube closure during early stages of pregnancy [28][29][30]. Anencephaly, SB (spina bifida), encephalocele, craniorachischisis and iniencephaly are the most common [31][32][33].…”
Section: Neural Tube Defectsmentioning
confidence: 99%